2021
DOI: 10.1002/ange.202107053
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation‐Induced Defects in MOF‐Derived Single Cobalt Atom@Carbon Electrocatalysts for Efficient Oxygen Reduction

Abstract: Developing transition metal single‐atom catalysts (SACs) for oxygen reduction reaction (ORR) is of great importance. Zeolitic imidazolate frameworks (ZIFs) as a subgroup of metal‐organic frameworks (MOFs) are distinguished as SAC precursors, due to their large porosity and N content. However, the activity of the formed metal sites is limited. Herein, we report a decarboxylation‐induced defects strategy to improve their intrinsic activity via increasing the defect density. Carboxylate/amide mixed‐linker MOF (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…And the addition of chelating elements can effectively improve the metal coordination environment, and the defect structure also contributes to anchor atoms. Yuan's team 96 proposed a defective MOF-derived SAC (Co@DMOF). They synthesized a rod-like crystalline MOF (DMOF) carrier by adding triethylenediamine (DABCO) as a support on the basis of the preparation method of IRMOF.…”
Section: The Synthesis and Coordination Environment Of Sacs Derived F...mentioning
confidence: 99%
See 1 more Smart Citation
“…And the addition of chelating elements can effectively improve the metal coordination environment, and the defect structure also contributes to anchor atoms. Yuan's team 96 proposed a defective MOF-derived SAC (Co@DMOF). They synthesized a rod-like crystalline MOF (DMOF) carrier by adding triethylenediamine (DABCO) as a support on the basis of the preparation method of IRMOF.…”
Section: The Synthesis and Coordination Environment Of Sacs Derived F...mentioning
confidence: 99%
“…In addition to Fe forming the Fe-N 4 -C site, Co also plays a role in a similar site structure. Yuan and colleagues 96 revealed the catalytic mechanism of the ORR at the active site of Co-N 4 in combination with DFT calculations. It was found that Co-N 4 -6r-c2 was the most favorable for the reaction.…”
Section: Active Sites Of Metal Atoms With Symmetrical Structures (M-n...mentioning
confidence: 99%
“…Recently, many highly efficient SACs (including Pt, Ir, Ru, Pd, Fe, Co, Ni, Mo, Mn, Cr, etc.) have been successfully prepared and used for probing ORR performance 196,281–315 . Zhu et al 281 designed and prepared an atomic Pt catalyst with Pt sites co‐coordinated to N and P on a carbon matrix (PtNPC, ~0.026 wt% Pt loading) using a polymerization impregnation carbonization method, as shown in Figure 24A.…”
Section: Advanced Energy Conversion To Reduce and Eliminate Co2 Emiss...mentioning
confidence: 99%
“…Yuan et al 294 prepared a defective single Co atom catalyst (Co@DMOF) by introducing a Co atom during the pyrolysis of Zn‐based MOF using a gas transport strategy. The AC HAADF‐STEM image and XAFS spectrum showed that Co species existed under the atomic dispersion condition and Co ions easily coordinated with four N atoms to form Co–N 4 active sites.…”
Section: Advanced Energy Conversion To Reduce and Eliminate Co2 Emiss...mentioning
confidence: 99%
“…This work provides a new pathway for the synthesis of defect‐rich SACs and elucidates that defects can effectively modulate the intrinsic activity of single‐atom catalysts. [ 75 ]…”
Section: Enhancing the Intrinsic Activity Of The Active Sitesmentioning
confidence: 99%